The Effectiveness Of Using Student Worksheet Accompanied by Hybridization Kit On The Discovery Learning Model - Putri, Nanda Lista; Erlina; Ifriany, Andi (Universitas Pendidikan Mandalika, 2025)
Chemistry learning, especially the topic of hybridization, is often considered difficult by students because the concepts are abstract and cannot be clearly visualized through 2D textbook images. This study aims to determine the effectiveness of using Student Worksheets (LKPD) accompanied by a Hybridization Kit (Hy-KIT) through the Discovery Learning model. The research employed a quantitative approach with a quasi-experimental design. The sample (N=72) was selected using purposive sampling and consisted of a control class (36 students) that used conventional worksheets (LKS) and an experimental class (36 students) that used LKPD with Hy-KIT. The research method used was a quasi-experimental design with a Nonrandomized Control Pretest–Posttest design. Data were collected through validated essay-type pretest and posttest questions. The novelty of this study lies in the integration of the 3D Hy-KIT media, which provides a real visualization of orbital shapes, with the Discovery Learning model. This combination serves as an alternative learning tool to significantly enhance students’ understanding of this abstract material. The results showed that both classes experienced improvement, but the experimental class demonstrated higher learning gains than the control class. The Effect Size (ES) calculation produced a value of 0.6, which falls into the medium category, indicating that the LKPD accompanied by Hy-KIT is effective in improving students’ understanding of hybridization concepts.